2020
DOI: 10.21203/rs.2.24656/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The lack of selection criteria for surgery in patients with non-colorectal non-neuroendocrine liver metastases

Abstract: Background: The benefit of surgery in patients with non-colorectal non-neuroendocrine liver metastases (NCRNNELM) remains controversial. At the population level, several statistical prognostic factors and scores have been proposed but inconsistently verified. At the patient level, no selection criteria have been demonstrated to guide individual therapeutic decision making. We aimed to evaluate potential individual selection criteria to predict the benefit of surgery in patients undergoing treatment for NCRNNEL… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Multiple liver metastases were the third factor having a negative impact on 5-year survival. In our study, 41% of patients had solitary liver metastases; in the literature, the percentage varies between 46 and 62% (Bohlok et al 2020;Hoffmann et al 2015;Lendoire et al 2007;Sano et al 2018;Takemura et al 2013;Yedibela et al 2005).…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Multiple liver metastases were the third factor having a negative impact on 5-year survival. In our study, 41% of patients had solitary liver metastases; in the literature, the percentage varies between 46 and 62% (Bohlok et al 2020;Hoffmann et al 2015;Lendoire et al 2007;Sano et al 2018;Takemura et al 2013;Yedibela et al 2005).…”
Section: Discussionsupporting
confidence: 40%
“…A short interval between diagnosis of the primary tumor and liver metastases also resulted independently in poorer 5-year survival. We saw in 65% of patients a tumor free interval of less than 24 months, others saw 50% or 51% (Bohlok et al 2020;Holzner et al 2018;Slotta et al 2014).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Patients have a slightly better prognosis if they do not have metastatic disease, if they have an adenocarcinoma component within the tumor, or if they respond to chemotherapy [ 23 ]. Unlike patients with non-colorectal non-neuroendocrine liver metastases [ 24 26 ], surgery, especially in the presence of metastatic disease, may not provide any survival benefit for most patients [ 23 ]. Fields et al [ 27 ] demonstrated that the total number of positive lymph nodes was an independent predictor of survival in patients with colon NENs.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, as patients have shown favourable outcome after ALPPS for CRLM that other secondary malignant lesions may benefit from it as well (7). However, benefit of resecting non-colorectal secondary liver lesions at all is still under debate, and although some reports provide supportive evidence, a selection bias must be anticipated as particularly young and otherwise healthy patients are preferred for treatments outside the mainstream (8,9).…”
mentioning
confidence: 99%